THE EFFECT OF AUDIT COMMITTEE CHARACTERISTICS ON FIRM CONTINUITY: THE MEDIATING ROLE OF EARNINGS MANAGEMENT – AN EMPIRICAL STUDY ON THE IRAQ STOCK EXCHANGE - Lect. Mustafa Mohammed Hussein; Dr. Mustafa Saeed Hasan (Scholar Express Journals, 2026)
The research aimed to test the impact of the audit committee's characteristics on the company's continuity, and the extent of the role played by earnings management when mediated by it. It examined the annual financial reports of a sample of 10 commercial banks listed on the Iraq Stock Exchange, and used the regression method to determine the direct relationship and structural equations to determine the indirect path. It concluded that mediating earnings management does not increase the independent effect on the dependent.
Keywords: Audit Committee Characteristics; Firm Continuity; Earnings Management